Analysis of Risk Factors for Severe Acute Respiratory Infection and Pneumonia and among Adult Patients with Acute Respiratory Illness during 2011-2014 Influenza Seasons in Korea - Kang, Seong Hui (Infect Chemother, 2016)
BACKGROUND: The World Health Organization recommends the surveillance of influenza-like illness (ILI) and severe acute respiratory infection (SARI) to respond effectively to both seasonal influenza epidemics and pandemics. In Korea, the “Hospital-based Influenza Morbidity and Mortality (HIMM)” surveillance system has been operated to monitor ILI and SARI occurrences. MATERIALS AND METHODS: A multi-center prospective observational study was conducted. Adult patients with acute respiratory infection (ARI) were enrolled during the 2011-12, 2012-2013, and 2013-2014 influenza seasons at the 10 university hospitals using the HIMM surveillance system. With respect to SARI and pneumonia development, risk profiles were analyzed in patients with ARI in Korea. RESULTS: A total of 5,459 cases were eligible for this analysis. Among 5,459 cases with ARI, 2,887 cases (52.9%) were identified that they had influenza infection. Among enrolled cases, 750 cases belonged to the SARI group, while 4,709 cases belonged to the non-SARI group. With respect to pneumonia development, 317 cases were accompanied by pneumonia, and 5,142 cases were not. Multivariate analyses revealed that the following factors were associated with an increased risk of SARI: Old age (≥65 years) (odds ratio [OR] 2.69, 95% confidence interval [CI] 2.2-3.32), chronic heart disease (CHD) (OR 2.24, 95% CI 1.68-2.98), cerebrovascular disease (CVD) (OR 1.49, 95% CI 1.05-2.10), chronic obstructive pulmonary disease (COPD) (OR 2.34, 95% CI 1.48-3.69), asthma (OR 2.33, 95% CI 1.62-3.36), chronic kidney disease (CKD) (OR 2.62, 95% CI 1.73-3.99), chronic liver disease (OR 1.71, 95% CI 1.04-2.81), and autoimmune diseases (OR 2.53, 1.57-4.08). Multivariate analyses revealed that the following factors were independent risk factors for pneumonia development: Old age (≥65 years) (OR 5.71, 95% CI 4.10-7.94), CHD (OR 1.54, 95% CI 1.07-2.22), COPD (OR 2.34, 95% CI 1.48-3.69), asthma (OR 2.33, 95% CI 1.62-3.36), CKD (OR 2.62, 95% CI 1.73-3.99), immunocompromised conditions (OR 3.12, 95% CI 1.47-6.62), and autoimmune diseases (OR 3.35, 95% CI 1.79-6.27). The risk of SARI and pneumonia was increased by the number of concurrent chronic medical conditions. CONCLUSION: The risk of SARI and pneumonia development among adult patient with ARI was significantly increased by the presence or number of concurrent chronic medical conditions in Korea.